1995
DOI: 10.1007/bf00189165
|View full text |Cite
|
Sign up to set email alerts
|

Role of transpiration suppression by evaporation of intercepted water in improving irrigation efficiency

Abstract: Sprinkler irrigation efficiency declines when applied water intercepted by the crop foliage, or gross interception (Igross), as well as airborne droplets and ponded water at the soil surface evaporate before use by the crop. However, evaporation of applied water can also supply some of the atmospheric demands usually met by plant transpiration. Any suppression of crop transpiration from the irrigated area as compared to a non-irrigated area can be subtracted from Igross irrigation application losses for a redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
79
5
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 22 publications
22
79
5
3
Order By: Relevance
“…14 by Thompson et al (1997) demonstrated that even with the short irrigation water contact time with a crop that is associated with a linear-move irrigation system, daily T is suppressed relative to T where an irrigation event does not occur. Tolk et al (1995) measured similar suppression with stem flow measurements and attributed the reduction to evaporation of canopy-intercepted water and microclimatic modification. Total ET for the day increased for the irrigated relative to the nonirri- gated scenarios due to the introduction of readily evaporable water to the soil and the low resistance to evaporation of free water on the leaves.…”
Section: Evaporation Based On Methods Of Water Applicationsupporting
confidence: 57%
See 2 more Smart Citations
“…14 by Thompson et al (1997) demonstrated that even with the short irrigation water contact time with a crop that is associated with a linear-move irrigation system, daily T is suppressed relative to T where an irrigation event does not occur. Tolk et al (1995) measured similar suppression with stem flow measurements and attributed the reduction to evaporation of canopy-intercepted water and microclimatic modification. Total ET for the day increased for the irrigated relative to the nonirri- gated scenarios due to the introduction of readily evaporable water to the soil and the low resistance to evaporation of free water on the leaves.…”
Section: Evaporation Based On Methods Of Water Applicationsupporting
confidence: 57%
“…Net crop canopy-interception loss was defined in Mc Naughton (1981) as the difference between the T from a nonirri gated area and the gross interception loss from an identical area that is irrigated. Tolk et al (1995) also noted that "transpiration recovery to near pre-irrigation levels was rapid, with additional transpiration suppression of 1-3% occurring only on days with high solar radiation. "…”
Section: Day Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…However, during daytime sprinkler irrigation, the crop microclimate is modified. Decreases of water vapor pressure deficit (VPD) and air temperature have been reported (Robinson, 1970;Steiner et al, 1983b;Tolk et al, 1995). The decrease in VPD would result in some reduction of the crop transpiration rates, leading to the conservation of soil water, which would otherwise be depleted by the crop (McNaughton, 1981;Steiner et al, 1983a).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this reduction of transpiration, some part of the application water losses during the irrigation event should not be considered as true losses. Consideration of net evaporation losses instead of gross evaporation losses would result in an increase of application efficiency for a given application depth (McNaughton, 1981;Tolk et al, 1995;Martínez-Cob et al, 2008). In addition to this beneficial effect of daytime sprinkler irrigation, the reduction in VPD would also result in a recovery of LWP during the irrigation events.…”
Section: Introductionmentioning
confidence: 99%